PENGGUNAAN MEDIA KAHOOT MELALUI MODEL DISCOVERY LEARNING PADA MATERI TEKNOLOGI INFORMASI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VIII SMPN 7 CILEGON - Bahrul Alam; Ade Fricticarani; Beni Junedi (STKIP Subang, 2026)
This study aims to enhance students' learning motivation in Grade VIII (30 students) at SMPN 7 Cilegon on Information Technology material using the Discovery Learning model supported by Kahoot media. The research employed a descriptive quantitative method. The results indicate that the use of Kahoot had a significant positive impact, improving students' learning motivation, understanding of the material, ability to retain information, and academic achievement through its engaging and interactive quiz format. In conclusion, Kahoot proves to be an effective ICT-based learning tool for sparking interest, facilitating material mastery, and enhancing overall teaching and learning quality at SMPN 7 Cilegon.